Державно-управлінська та фінансова діяльність на українських територіях (XVIII – перша половина ХІХ століття) - Карп’як, О. О.; Karpiak, O. O. (Право і суспільство. - 2020. - № 3, ч. 2. - С. 3-8, 2020)
Проаналізовано державно-управлінська та фінансова діяльність на українських територіях у XVIII –першій половині XІX століття. Доведено, що узагальнюючи реформи та державно-фінансову діяльність в представлені історико-правові рамки, варто виділити її головні напрямки, зокрема: скоротити до мінімуму всі відділи державного кредитування промисловості і сільського господарства, що тим самим має привести до зниження ставки процента; звести до мінімуму використання іноземних позик; збільшувати державні надходження в бюджет не через прямі податки, а шляхом непрямих зборів, зокрема, за допомогою відкупів і митних зборів, які вимагають мінімальних адміністративних витрат; забезпечення бюрократизації та централізації державного управління, сприяти переселенню селян і добровільного звільнення їх поміщиками від кріпацтва тощо.

The scientific article is devoted to the research and complex analysis of public administration and financial activities in the Ukrainian territories in the XVIII-first half of the XIX century. It argued that finance as part of social relations, and relations of a special kind, allow themselves to show the state economy in all its manifestations as a whole. They as an indicator serve as a determinant of civilization and development of society, the state as a whole and its institutions in particular. Law, or rather, legislation is a means to achieve the goals set before the government and society. The purpose of financial science is to study state economic activity in its historical development, to analyze the causes of the emergence and modification of financial institutions, and to discover the evolutionary laws of the state economy. At the same time, the purpose of the science of the history of the state and law is to study the organizational and legal foundations of the financial system as the skeleton of the state mechanism. Finance, like no other relationship, allows us to trace the interactions and interpenetration of state and law. It proved that summarizing the reforms and public financial activities in the presented historical and legal framework, it is necessary to highlight its main directions, in particular: to minimize all departments of public lending to industry and agriculture, which should lead to lower interest rates; minimize the use of foreign loans; increase state revenues not through direct taxes, but through indirect fees, in particular, through ransoms and customs duties, which require minimal administrative costs; ensuring bureaucratization and centralization of public administration, facilitating the resettlement of peasants and the voluntary liberation of their landlords from serfdom, etc. The creation of a centralized financial management system took a long and difficult time, but given the socio-political and economic circumstances in the country at the time, the results of ministerial reform and financial reform called not only significant but also progressive. The manifestos of 1802 and 1811 were the basis for the functioning of the financial system in the first half of the nineteenth century, but their disadvantage was the combination in one document of regulation of various spheres of social relations (administrative, financial, etc.). The consequence of the use of such legal techniques was the need to clarify and supplement the existing financial regulations with new ones, which further hampered the financial and managerial activities through constant changes and improvements.

Проанализирована государственно-управленческая и финансовая деятельность на украинских территориях в XVIII – первой половине XIX века. Доказано, что обобщая реформы и государственно-финансовую деятельность в представленные историко-правовые рамки следует выделить ее главные направления, в частности: сократить до минимума все отделы государственного кредитования промышленности и сельского хозяйства, что тем самым должно привести к снижению ставки процента; свести к минимуму использование иностранных ссуд; увеличивать государственные поступления в бюджет не через прямые налоги, а путем косвенных сборов, в частности, посредством откупов и таможенных пошлин, требующих минимальных административных расходов; обеспечение бюрократизации и централизации государственного управления, способствовать переселению крестьян и освобождению их помещиками от крепостного права и т.д.
State-management and financial activity in the Ukrainian territories (XVIII – first half of the 19th century)
Карп’як, О. О. Державно-управлінська та фінансова діяльність на українських територіях (XVIII – перша половина ХІХ століття) / Карп’як О. О. // Право і суспільство. - 2020. - № 3, ч. 2. - С. 3-8. - DOI: https://doi.org/10.32842/2078-3736/2020.3-2.1.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; фінанси; finances; финансы; фінансова діяльність; financial activity; финансовая деятельность; Історія. History. История; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; державно-управлінська діяльність; state management activity; государственно-управленческая деятельность